The Water-Energy-Food Nexus: Opportunities for the Eastern Nile - Ringler, Claudia; Berga, Helen (2017)
Presented by Claudia Ringler, IFPRI, and Helen Berga, ZEF, at the Nile Basin Development Forum on October 24, 2017.